Genomic Response to Vitamin D Supplementation in the Setting of a Randomized, Placebo-Controlled Trial - Berlanga-Taylor, Antonio J. (EBioMedicine, 2018)
BACKGROUND: Vitamin D deficiency has been associated with multiple diseases, but the causal relevance and underlying processes are not fully understood. Elucidating the mechanisms of action of drug treatments in humans is challenging, but application of functional genomic approaches in randomized trials may afford an opportunity to systematically assess molecular responses. METHODS: In the Biochemical Efficacy and Safety Trial of Vitamin D (BEST-D), a double-blind, placebo-controlled, dose-finding, randomized clinical trial, 305 community-dwelling individuals aged over 65 years were randomly allocated to treatment with vitamin D(3) 4000 IU, 2000 IU or placebo daily for 12 months. Genome-wide genotypes at baseline, and transcriptome and plasma levels of cytokines (IFN-γ, IL-10, IL-8, IL-6 and TNF-α) at baseline and after 12 months, were measured. The trial had >90% power to detect 1.2-fold changes in gene expression. FINDINGS: Allocation to vitamin D for 12-months was associated with 2-fold higher plasma levels of 25-hydroxy-vitamin D (25[OH]D, 4000 IU regimen), but had no significant effect on whole-blood gene expression (FDR < 5%) or on plasma levels of cytokines compared with placebo. In pre-specified analysis, rs7041 (intron variant, GC) had a significant effect on circulating levels of 25(OH)D in the low dose, but not in the placebo or high dose vitamin D regimen. A gene expression quantitative trait locus analysis (eQTL) demonstrated evidence of 31,568 cis-eQTLs (unique SNP-probe pairs) among individuals at baseline and 34,254 after supplementation for 12 months (any dose). No significant associations involving vitamin D supplementation response eQTLs were found. INTERPRETATION: We performed a comprehensive functional genomics and molecular analysis of vitamin D supplementation in a randomized, placebo-controlled trial. Although this study was limited to mostly Caucasian individuals aged over 65 years, the results differ from many previous studies and do not support a strong effect of vitamin D on long-term transcriptomic changes in blood or on plasma cytokine levels. The trial demonstrates the feasibility of applying functional genomic and genetic approaches in randomized trials to assess molecular and individual level responses. KEY RESULT: Supplementation with high-dose vitamin D in older people for 12 months in a randomized, placebo-controlled trial had no significant effect on gene expression or on plasma concentrations of selected cytokines. TRIAL REGISTRATION: SRCTN registry (Number 07034656) and the European Clinical Trials Database (EudraCT Number 2011-005763-24).